Pre-service Early Childhood Teachers' Perceptions on Digital Media for Language Creativity Stimulation - Anies Listyowati; Titah Kinasih (Journal of Early Childhood Education Perspectives, 2025)
The integration of digital media in early childhood education has become increasingly prevalent, yet understanding pre-service teachers' perceptions toward its role in stimulating language creativity remains limited. This mixed-methods study examined 95 pre-service early childhood teachers' perceptions of digital media for language creativity stimulation. Using a structured questionnaire with 21 Likert-scale items and three open-ended questions, we assessed six dimensions: importance of language creativity, readiness and competence, perceptions of digital media, teaching methods, frequency and effectiveness, and barriers and challenges. Quantitative data were analyzed using descriptive statistics, while qualitative responses underwent thematic analysis. Results revealed an overall high perception (M = 4.353), with the highest scores for importance of language creativity (M = 4.703) and readiness and competence (M = 4.532). Participants demonstrated strong awareness of digital media benefits, with 77.9% emphasizing vocabulary enhancement, while acknowledging significant challenges including infrastructure limitations (41.1%) and content appropriateness concerns (38.9%). The study contributes to understanding pre-service teachers' preparedness for technology integration in developing country contexts and highlights the need for comprehensive technological pedagogical content knowledge development in teacher education programs to support effective digital media integration in early childhood language education.